Immuno-PET: Design options and clinical proof-of-concept - Lugat, Alexandre; Bailly, Clément; Chérel, Michel; Rousseau, Caroline; Kraeber-Bodéré, Françoise; Bodet-Milin, Caroline; Bourgeois, Mickaël (Frontiers in Medicine, 2022)
Radioimmunoconjugates have been used for over 30 years in nuclear medicine applications. In the last few years, advances in cancer biology knowledge have led to the identification of new molecular targets specific to certain patient subgroups. The use of these targets in targeted therapies approaches has allowed the developments of specifically tailored therapeutics for patients. As consequence of the PET-imaging progresses, nuclear medicine has developed powerful imaging tools, based on monoclonal antibodies, to in vivo characterization of these tumor biomarkers. This imaging modality known as immuno-positron emission tomography (immuno-PET) is currently in fastest-growing and its medical value lies in its ability to give a non-invasive method to assess the in vivo target expression and distribution and provide key-information on the tumor targeting. Currently, immuno-PET presents promising probes for different nuclear medicine topics as staging/stratification tool, theranostic approaches or predictive/prognostic biomarkers. To develop a radiopharmaceutical drug that can be used in immuno-PET approach, it is necessary to find the best compromise between the isotope choice and the immunologic structure (full monoclonal antibody or derivatives). Through some clinical applications, this paper review aims to discuss the most important aspects of the isotope choice and the usable proteic structure that can be used to meet the clinical needs.